TAXPAYERS’ PERCEPTION OF TAX EVASION STUDIED FROM TAX KNOWLEDGE, TAX FAIRNESS, AND TAX DICRIMINATION - Nugaha, Bima Aditya; Hajanirina, Andrianantenaina (RIMA - Research In Management and Accounting, 2020)
This paper attempts to study taxpayers’ perception on tax evasion while tax knowledge, tax fairness, and tax discrimination are considered. It sampled individual taxpayers who are registered in the tax office of Sekayu Regency, Palembang. Purposive sampling is used and sample of 200 respondents are obtained. Data collection is done by questionnaire method distributed to respondents. The results of this study indicate that tax knowledge, tax fairness, and tax discrimination are significantly associated with perception of tax evasion.